Fe-Cr/CNTs nanocomposite feedstock powders produced by chemical vapor deposition for thermal spray coatings - S. Moonngam (2018)
© 2016 Elsevier B.V. The carbon nanotubes (CNTs) were synthesized using a traditional chemical vapor deposition technique directly on Fe-13Cr (wt%) feedstock powder for thermal spray coating without catalyst. CNTs were grown at a temperature of 500, 550, 600, 650, 700, 750 and 800 °C for 60 min and at 650 °C for 30, 45, 60 and 90 min under a controlled atmosphere with ethanol as a carbon source. The synthesized powders were characterized using various techniques: (1) Scanning Electron Microscope (SEM); (2) X-ray Diffraction (XRD); (3) Raman Spectroscopy; (4) Energy-dispersive Spectroscopy (EDS); and (5) Transmission Electron Microscope (TEM). The presence and quality of the CNTs were analyzed by Raman Spectroscopy in which D band and G band were clearly seen at 2187 cm− 1and 2653 cm− 1respectively. It was found that the CNTs had an average diameter of 32 to 81 nm and a length of 7 to more than 100 nm. The results show that CNTs can be grown on Fe-13Cr thermal sprayed feedstock powder with an optimal condition for the synthetization of CNTs at 600–650 °C for 60 min with homogeneous and uniform distribution of CNTs. The FeCr/CNTs composite powder was successfully sprayed using Low Velocity Oxy-Fuel (LVOF) that confirmed the potential for use as a new coating.